Cerium-zirconium based composite oxide with gradient element distribution and preparation method thereof

JP7634578B2Active Publication Date: 2025-02-21GRIREM ADVANCED MATERIALS CO LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022581504
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-17
Filing Date
2021-08-27
Publication Date
2025-02-21
Estimated Expiration
2041-08-27

AI Technical Summary

Benefits of technology

【0033】 要約すると、本発明は、元素が勾配分布したセリウム-ジルコニウム系複合酸化物及びその調製方法、前記複合酸化物を用いた触媒システム、前記触媒システムを用いて排ガスの浄化を行う触媒装置、及び自動車排ガスの浄化、産業排ガスの処理又は触媒燃焼における前記触媒システム又は触媒装置の適用を提供する。本発明は、段階的沈殿法により前記元素が勾配分布したセリウム-ジルコニウム系複合酸化物を調製することにより、第1に、ジルコニウムリッチ成分を沈殿させ、先に沈殿したジルコニウムリッチ成分は熱安定が高い粒子構造と粒子堆積構造を形成でき、高温処理後のジルコニウムの表面偏析を緩和し、粒子間の元素の移動を減少させ、第2に、セリウムリッチ成分を後に沈殿させ、粒子表層のセリウム含有量を高め、セリウム元素の利用率を向上させ、酸素貯蔵量と酸素貯蔵·排出速度を速める。この方法により調製された複合酸化物は、セリウム-ジルコニウム系複合酸化物を含む触媒を長時間使用することによる、セリウム-ジルコニウム系複合酸化物の熱安定性と酸素貯蔵·排出性能の要求を満たすように、高い熱安定性と高い酸素貯蔵·排出性能を兼ね備える。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634578000005
    Figure 0007634578000005
  • Figure 0007634578000006
    Figure 0007634578000006
  • Figure 0007634578000001
    Figure 0007634578000001
Patent Text Reader

Abstract

The present invention relates to a cerium-zirconium composite oxide with a gradient distribution of elements, a method for producing the same, a catalytic system using the composite oxide, a catalytic device for air purification using the catalytic system, and the application of the catalytic system or device in automobile exhaust gas purification, industrial exhaust gas treatment, or catalytic combustion. The present invention prepares the cerium-zirconium composite oxide with a gradient distribution of elements by a stepwise precipitation method. By precipitating the zirconium-rich component first, a highly thermally stable particle structure and particle deposition structure can be formed, which reduces the surface segregation of zirconium after high-temperature treatment and reduces the interparticle element migration. By precipitating the cerium-rich component later, the cerium content in the particle surface layer can be increased, improving the utilization rate of cerium element and increasing the oxygen storage capacity and oxygen storage / release rate. The composite oxide prepared by this method combines high thermal stability and high oxygen storage / release performance, meeting the requirements for thermal stability and oxygen storage / release performance of cerium-zirconium composite oxides during long-term use of catalysts containing the cerium-zirconium composite oxide.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to catalysts and the related field of their preparation, and in particular to a cerium-zirconium composite oxide with gradient element distribution that can be used in fields such as automobile exhaust gas purification, industrial exhaust gas treatment, and catalytic combustion, and a method for preparing the same. [Background technology]

[0002] In recent years, as people's demands for environmental air quality have increased, the requirements for gas emission regulations for automobile exhaust gases and volatile organic exhaust gases have become increasingly strict, and gas conversion is required for the use of traditional fossil energy sources. The cerium-zirconium composite oxides used in this process must have a stable structure and rapid oxygen storage and release capabilities. It is known that zirconium-rich components have better thermal stability than cerium-rich components, and that cerium-rich components are better at storing and releasing oxygen than zirconium-rich components. In addition, during actual use, the components that exhibit the oxygen storage and release function of cerium-zirconium composite oxides are mainly distributed on the surface layer of the particles.

[0003] In order to achieve both good thermal stability and oxygen storage and release capacity, it has been found that constructing a core-shell structure by stepwise precipitation is advantageous for improving the ability to prevent sintering. Patent document CN101091914B proposes a method of first precipitating zirconium salt and other rare earth metal salts other than cerium, and then precipitating cerium salt, which can improve the specific surface area heat resistance at high temperatures (1100°C / 3h) of cerium-zirconium composite oxide. However, since the outer layer only contains cerium and is prone to sintering, the specific surface area heat resistance at high temperatures is still unfavorable (20-22m2) after heat treatment at 1100°C for 3h. 2In patent document CN102883808A, zirconium and cerium compounds, or these compounds and rare earth elements other than cerium, are first precipitated, where the amount of rare earth elements other than cerium is less than that to obtain the desired compound, and the remaining amount of elements contained in the desired compound is precipitated later, and after calcination at 1100°C for 4 hours by this method, a specific surface area of ​​25 m 2 It has been proposed to obtain a cerium-zirconium-based composite oxide having a cerium-zirconium complex oxide with a cerium-zirconium complex oxide content of 1000 / g or more. However, since only the doped element is precipitated later, it is insufficient to delay the segregation of the element inside the particle. This cerium-zirconium-based composite oxide showed phase separation after sintering at 1000°C for 4 hours, and the high-temperature thermal stability of the cerium-zirconium material was greatly reduced. Patent document CN103962120A also proposes a method of first precipitating cerium-zirconium and then partially precipitating yttrium and / or rare earth metal compounds later, but the proportion of cerium oxide is limited to oxides based on zirconium, cerium and yttrium between 3% and 15%, and the precipitant does not contain zirconium, making it difficult to have good thermal stability at high temperatures. Patent document CN107427822A proposes an exhaust purification catalyst of a core-shell carrier and a preparation method thereof. Its core-shell structure is formed by applying a load coating method, and the structure is a core-shell structure, the elements are layered in the radial direction, and there is no gradient distribution of the elements. The preparation method is a two-step synthesis, in which the core is synthesized in the first step, and then the shell layer is prepared by applying a load coating method based on the core particles, and since the inner and outer layers are layered in the core-shell structure, the elements are discontinuous in the radial direction, and there is no gradient distribution of the elements. Patent document CN103191711A proposes to first synthesize an alkaline zirconium sulfate composite salt precursor, and then mix and precipitate cerium salt and rare earth metal salt to obtain a cerium-zirconium composite oxide. After heat treatment at 1100°C for 3 hours, this composite oxide has a specific surface area of ​​25m 2 / g and oxygen storage below 400 μmol O2 / g, which is still low.

[0004] Therefore, it is necessary to develop a cerium-zirconium based composite oxide that has a gradient distribution of elements to retard elemental segregation at high temperatures, improve the utilization rate of cerium element, and maintain a stable phase structure and higher oxygen storage capacity even after heat treatment at 1100°C. Summary of the Invention [Problem to be solved by the invention]

[0005] Based on the above-mentioned circumstances of the prior art, the object of the present invention is to provide a cerium-zirconium-based composite oxide having gradient element distribution and a preparation method thereof. This preparation method can establish a gradient element distribution structure with an inner layer rich in zirconium and an outer layer rich in cerium, and the cerium-zirconium composite oxide exhibits high thermal stability and oxygen storage and release capacity, and can maintain a stable particle structure even after use in a high-temperature environment, and can maintain a large specific surface area and high oxygen storage capacity, and can be used in catalytic fields such as automobile exhaust gas purification, volatile organic matter purification, catalytic combustion of natural gas, and steam reforming of hydrocarbons. [Means for solving the problem]

[0006] In order to achieve the above object, according to one aspect of the present invention, there is provided a cerium-zirconium-based composite oxide having an element gradient distribution, which contains cerium element and zirconium element, and in which the cerium element and the zirconium element are distributed in a gradient manner from the inside to the outside of a particle.

[0007] Furthermore, the composite oxide has a higher cerium oxide content on the particle surface than the entire composite oxide, a lower zirconium oxide content on the particle surface than the entire composite oxide, and the cerium content gradually increases from the inside to the outside in the radial direction of the particle, and the zirconium content gradually decreases from the inside to the outside in the radial direction of the particle.

[0008] The composite oxide also includes the following, which are expressed as oxides: 10% to 80% cerium oxide in molar terms, 15% to 80% zirconium oxide in molar terms, 0% to 20% of other oxides on a molar basis.

[0009] The composite oxide also includes the following, which are expressed as oxides: 30% to 60% cerium oxide in molar terms, 30% to 60% zirconium oxide on a molar basis.

[0010] The other oxides are a combination of one or more elements selected from the group consisting of rare earth elements other than cerium and non-rare earth metal elements other than zirconium, and the content of the other oxides in the composite oxide is 2% to 15% in terms of moles, and the oxides of rare earth elements other than cerium account for 70% to 100% of the other oxides.

[0011] Moreover, the composite oxide has a hafnium oxide content of 0.05% to 2% in terms of moles.

[0012] The rare earth elements other than cerium and the non-rare earth metal elements other than zirconium include at least one combination of lanthanum, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium, yttrium, hafnium, aluminum, barium, manganese, and copper.

[0013] The rare earth elements other than cerium and the non-rare earth metal elements other than zirconium are a combination of one or more of lanthanum, praseodymium, neodymium, europium, yttrium, hafnium, aluminum, and manganese.

[0014] The gradient distribution further includes an element gradient distribution of one or more rare earth elements other than cerium and / or non-rare earth elements other than zirconium, and the gradient distribution is such that the content of the element gradually decreases or gradually increases from the inside to the outside in the radial direction of the particle.

[0015] The gradient distribution further includes a gradient distribution in which the content of the rare earth element other than cerium gradually increases from the inside to the outside in the radial direction of the particle.

[0016] The rare earth elements other than cerium and the non-rare earth metal elements other than zirconium are a combination of one or more of lanthanum, praseodymium, neodymium, europium, yttrium, hafnium, aluminum, and manganese.

[0017] The composite oxide is After heat treatment in air at 1000°C for 4 hours, the specific surface area is 55-65m 2 / g, After heat treatment in air at 1100°C for 4 hours, the specific surface area is 35 to 55 m 2 / g.

[0018] Moreover, the composite oxide contains pores of 2 nm to 100 nm, the total pore volume is between 0.1 mL / g and 0.5 mL / g, and the static oxygen storage capacity is ≧500 μmol O2 / g.

[0019] Moreover, after calcination at 1100°C for 4 hours in air, the composite oxide contains pores of 10 nm to 30 nm, the total pore volume is between 0.03 mL / g and 0.2 mL / g, and the static oxygen storage capacity is ≧400 μmol O2 / g.

[0020] According to a second aspect of the present invention, there is provided a method for preparing a cerium-zirconium based composite oxide having an element gradient distribution, comprising the steps of: Step (a): In the first step of precipitation, an alkaline substance is mixed with a mixed solution A containing a cerium salt, a zirconium salt, or a cerium salt, a zirconium salt and, optionally, a rare earth salt other than cerium and a non-rare earth metal salt other than zirconium, and the mixture is stirred and reacted to obtain a precipitate slurry containing the above elements. Step (b): In the second precipitation step, a mixture B of a cerium salt, a zirconium salt, or a cerium salt, a zirconium salt, and optionally one or more metal salts selected from a rare earth salt other than cerium and a non-rare earth metal salt other than zirconium, and an alkaline substance to be added at the same time, is added to the slurry to cause precipitation, and the mixture is filtered and washed. Water is added to adjust the slurry, and a precipitate slurry containing cerium, zirconium, or cerium, zirconium, and other elements is obtained. Step (c): The slurry obtained in step (b) is heated, a modifier is added thereto, and the mixture is filtered to obtain a cerium-zirconium composite precipitate. The precipitate is then fired at 600°C to 950°C to obtain the cerium-zirconium composite oxide.

[0021] In addition, the zirconium in the mixed solution A accounts for 50% or more of the total zirconium content in terms of molar weight, and the cerium in the mixed solution B accounts for 50% or more of the total cerium content.

[0022] The content of zirconium in the mixed solution A relative to the total zirconium content is 60 to 80% in terms of molar weight, and the content of cerium in the mixed solution B is 60 to 80% of the total cerium content.

[0023] The salts other than zirconium in the mixed solution A and the mixed solution B are a combination of one or more of nitrates, chlorides, sulfates, and acetates.

[0024] The zirconium salt in the mixed solution A and the mixed solution B is a combination of one or more of zirconium oxide nitrate, zirconium oxide sulfate, zirconium oxide chloride, and zirconium acetate.

[0025] The alkaline substance is a combination of one or more of sodium hydroxide, ammonium hydroxide, potassium hydroxide, urea, ammonium carbonate, sodium carbonate, and sodium bicarbonate.

[0026] In addition, each of the mixed liquid A and the mixed liquid B contains 0.2 to 3 moles of ligand ions per mole of zirconium element, and the ligand ions are sulfate anions. The sulfate anions are provided by adding sulfuric acid or a sulfate salt to the mixed liquid A and the mixed liquid B.

[0027] In addition, in the precipitation in the first step, the amount of alkaline substance used is 0.8 to 1.5 times the theoretical amount required for precipitation of cations, and in the precipitation in the second step, the pH needs to be controlled within a preset range.

[0028] The ratio of the ligand ions to the zirconium ions is between 0.5 and 2.5.

[0029] The modifier includes at least one of anionic surfactants, nonionic surfactants, polyethylene glycol, carboxylic acids and their salts, and carboxymethylated fatty alcohol ethoxy compound surfactants.

[0030] According to a third aspect of the present invention, there is provided a catalyst system comprising the cerium-zirconium-based composite oxide provided in the first aspect of the present invention or the cerium-zirconium-based composite oxide prepared by the preparation method provided in the second aspect of the present invention, and one or more of aluminum oxide, a transition metal, a noble metal, and a support.

[0031] According to a fourth aspect of the present invention, there is provided a catalyst device for purifying exhaust gas using the catalyst system provided in the third aspect of the present invention.

[0032] The catalytic system provided in the third aspect of the present invention or the catalytic device provided in the fourth aspect of the present invention is applied to the purification of automobile exhaust gas, the treatment of industrial exhaust gas or catalytic combustion. Effect of the Invention

[0033] In summary, the present invention provides a cerium-zirconium composite oxide having gradient distribution of elements and a preparation method thereof, a catalyst system using said composite oxide, a catalyst device using said catalyst system for purifying exhaust gas, and application of said catalyst system or catalyst device in purifying automobile exhaust gas, treating industrial exhaust gas or catalytic combustion. The present invention prepares the cerium-zirconium composite oxide having gradient distribution of elements by a stepwise precipitation method, which firstly precipitates a zirconium-rich component, and the zirconium-rich component precipitated first can form a particle structure and particle deposition structure with high thermal stability, which alleviates the surface segregation of zirconium after high-temperature treatment and reduces the movement of elements between particles, and secondly, precipitates a cerium-rich component later, which increases the cerium content of the particle surface layer, which improves the utilization rate of cerium element, and increases the oxygen storage amount and the oxygen storage and release rate. The composite oxide prepared by this method has both high thermal stability and high oxygen storage / release performance, which satisfies the requirements for thermal stability and oxygen storage / release performance of cerium-zirconium composite oxide when a catalyst containing the cerium-zirconium composite oxide is used for a long period of time. [Brief description of the drawings]

[0034] [Figure 1] 1 is a flow chart showing a method for preparing a cerium-zirconium based composite oxide having gradient element distribution according to the present invention. [Diagram 2] FIG. 2 is a HAADF-STEM-EDS diagram of a cerium-zirconium based composite oxide having a cerium-zirconium gradient distribution according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] In order to make the objectives, technical solutions and advantages of the present invention clearer and more obvious, the present invention will be described in detail below in combination with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are merely illustrative and do not limit the scope of the present invention. In addition, in the following description, descriptions of known structures and technologies are omitted so as not to unnecessarily confuse the concept of the present invention.

[0036] In the present invention, various physical properties are measured using the methods shown below. (1) Specific surface area, pore diameter, pore volume The specific surface area is measured by the BET method using a specific surface area and pore size analyzer (Quadrasorb Evo).

[0037] (2) Static oxygen storage capacity (OSC) The oxygen storage capacity is measured using a chemical adsorption meter (ChemBET Pulsar TPR / TPD) based on the isothermal oxygen titration method. More specifically, 0.03 g of powder is fully reduced by heating to 800°C in a 5% hydrogen / argon gas flow and maintaining it for 60 minutes. The temperature is then lowered to 500°C in helium gas, and after the temperature stabilizes, pulse titration of oxygen is performed until saturation is reached, and the static oxygen storage capacity is calculated from the amount of oxygen absorbed.

[0038] (3) Gradient distribution of elements The gradient distribution of elements is measured by X-ray fluorescence spectroscopy (XRF), X-ray photoelectron spectroscopy (XPS), high angle annular dark field scanning transmission electron spectroscopy (HAADF-STEM-EDS) line scanning and surface scanning feature analysis. XRF analysis can obtain the element content of the whole material, XPS analysis can obtain the element content and ratio of the particle surface, and HAADF-STEM-EDS can obtain the whole element distribution in the particle diameter direction.

[0039] According to a first aspect of the present invention, there is provided a cerium-zirconium based composite oxide having gradient distribution of elements, the composite oxide containing cerium and zirconium, the cerium and zirconium elements exhibiting a gradient distribution from the inside to the outside in the particles. Here, exhibiting a gradient distribution means that the content of cerium oxide on the particle surface of the composite oxide is higher than the content of cerium oxide in the entire composite oxide, the content of zirconium oxide on the particle surface is lower than the content of zirconium oxide in the entire composite oxide, the content of cerium gradually increases from the inside to the outside in the radial direction of the particle, and the content of zirconium gradually decreases from the inside to the outside in the radial direction of the particle. The thermal stability of the zirconium-rich component is superior to that of the cerium-rich component, but the oxygen storage and release performance of the cerium-rich component is superior to that of the zirconium-rich component. In addition, during actual use, the components that exert the oxygen storage and release properties of the cerium-zirconium composite oxide are distributed mainly on the particle surface, so the structure of this composite oxide is designed to exhibit a gradient distribution, and this oxide can achieve both high temperature thermal stability and high oxygen storage and release performance.

[0040] The composite oxide also includes the following, which are expressed as oxides: 10% to 80% cerium oxide in molar terms, preferably 30% to 60% cerium oxide in molar terms; 15% to 80% by mole of zirconium oxide, preferably 30% to 60% by mole of zirconium oxide, and 0% to 20% of other oxides on a molar basis.

[0041] Here, the other oxide means a combination of one or more elements selected from rare earth elements other than cerium and non-rare earth metal elements other than zirconium. In the composite oxide, the content of the other oxide is 0% to 20%, preferably 2% to 15%, in molar terms, and the content of the oxide of a rare earth element other than cerium in the other oxide is 0% to 100%, preferably 70% to 100%. The zirconium oxide may be doped with hafnium oxide, and the content of hafnium oxide in the zirconium oxide is 0.5% to 2% in molar terms.

[0042] Here, the rare earth elements other than cerium and the non-rare earth metal elements other than zirconium include at least one combination of lanthanum, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium, yttrium, hafnium, aluminum, barium, manganese, and copper, and preferably one or more combinations of lanthanum, praseodymium, neodymium, europium, yttrium, hafnium aluminum, and manganese.

[0043] The gradient distribution further includes a gradient distribution of one or more elements selected from the group consisting of rare earth elements other than cerium and non-rare earth metal elements other than zirconium, and this gradient distribution means that the content of the element gradually decreases or gradually increases from the inside to the outside in the radial direction of the particle.

[0044] The gradient distribution of the rare earth elements other than cerium and the non-rare earth metal elements other than zirconium is a combination of one or more of lanthanum, praseodymium, neodymium, europium, yttrium, hafnium, aluminum, and manganese.

[0045] The composite oxide has a specific surface area of ​​55 to 65 m after heat treatment in air at 1000°C for 4 hours. 2 / g, and the specific surface area after heat treatment in air at 1100°C for 4 hours is 35 to 55 m 2 / g, which is an excellent specific surface area.

[0046] The composite oxide contains pores of 2 nm to 100 nm, a total pore volume between 0.1 mL / g and 0.5 mL / g, and an oxygen storage capacity of ≧500 μmol O2 / g. The composite oxide contains pores of 10 nm to 30 nm, a total pore volume between 0.03 mL / g and 0.2 mL / g, and an oxygen storage capacity of ≧400 μmol O2 / g after calcination at 1100° C. in air for 4 hours.

[0047] In a second embodiment of the present invention, a method for preparing a cerium-zirconium-based composite oxide with gradient element distribution is provided, the preparation method being a stepwise precipitation method, the flow diagram of which is shown in FIG. 1, and including the following steps:

[0048] Step (a): In the first precipitation step, an alkaline substance is mixed with a mixed solution A containing a cerium salt, a zirconium salt, or a cerium salt, a zirconium salt, and optionally one or more metal salts selected from rare earth salts other than cerium and non-rare earth metal salts other than zirconium, and the mixture is stirred and reacted to obtain a slurry of a precipitate containing the metals. Here, the zirconium in the mixed solution A may account for 50% or more, preferably 60 to 80%, of the total amount of zirconium in terms of molar weight.

[0049] Step (b): The precipitation in the second step is carried out by adding a mixed solution B of cerium salt, zirconium salt, or cerium salt, zirconium salt, and optionally one or more metal salts selected from rare earth salts other than cerium and non-rare earth metal salts other than zirconium, and an alkaline substance to be added at the same time to the slurry, followed by precipitation, filtering and washing, and adding water to adjust the slurry, to obtain a precipitate slurry containing cerium, zirconium, or cerium, zirconium, and other metals. Here, the cerium in the mixed solution B may account for 50% or more of the total cerium amount in terms of molar weight, and preferably 60% to 80%.

[0050] Step (C): The slurry is heated, a modifier is added thereto, and then filtered to obtain a cerium-zirconium composite precipitate, which is then calcined at 600°C to 950°C to obtain the cerium-zirconium composite oxide.

[0051] In this embodiment of the present invention, the composite oxide is prepared by a stepwise precipitation method, and the zirconium-rich component is precipitated first, which can form a crystal structure and particle deposition structure with high thermal stability, and can alleviate the surface segregation of zirconium after high-temperature treatment and reduce the movement of elements between particles. The cerium-rich component is precipitated later, which can increase the cerium content of the particle surface layer, improve the utilization rate of cerium element, and further increase the oxygen storage amount and oxygen storage and release rate. Therefore, the composite oxide prepared by this method has both high thermal stability and high oxygen storage and release performance, so as to meet the requirements of the thermal stability and oxygen storage and release performance of the cerium-zirconium-based composite oxide caused by the long-term use of the catalyst containing the cerium-zirconium-based composite oxide.

[0052] The salts other than zirconium in the mixed solutions A and B are a combination of one or more of nitrates, chlorides, sulfates, and acetates. The zirconium salts in the mixed solutions A and B are a combination of one or more of zirconium nitrate oxide, zirconium sulfate oxide, zirconium chloride oxide, and zirconium acetate. The alkaline substance is a combination of one or more of sodium hydroxide, ammonium hydroxide, potassium hydroxide, urea, ammonium carbonate, sodium carbonate, and sodium bicarbonate.

[0053] JPEG0007634578000001.jpg26170

[0054] The amount of alkaline substance used in the precipitation in the first step is 0.8 to 1.5 times the theoretical amount required for precipitation of cations, and the pH in the precipitation in the second step must be controlled within the range of 6 to 12.

[0055] The modifier includes at least one of anionic surfactants, nonionic surfactants, polyethylene glycol, carboxylic acids and their salts, and carboxymethylated fatty alcohol ethoxy compound surfactants.

[0056] FIG. 2 is a typical spherical aberration corrected high angle annular dark field scanning transmission electron spectroscopy (HAADF-STEM-EDS) diagram of the cerium-zirconium based composite oxide with gradient distribution of elements of the present invention, and the element distribution status of the particles is shown in the figure. The red dots indicate the signal of zirconium element, and the green dots indicate the signal of cerium element. It can be seen from FIG. 2 that the green signal is concentrated on the particle surface, and the red signal is concentrated inside the particle. This shows that the content of cerium element and zirconium element is different between the inside of the particle and the surface of the particle, and the content of cerium increases from the inside to the outside of the particle, and the content of zirconium decreases from the inside to the outside of the particle. This shows that a cerium-zirconium based composite oxide with gradient distribution of elements has been synthesized by the stepwise precipitation method.

[0057] A third embodiment of the present invention provides a catalyst system including the cerium-zirconium-based composite oxide provided in the first embodiment or the cerium-zirconium-based composite oxide prepared by the preparation method provided in the second embodiment, and one or more of aluminum oxide, a transition metal, a noble metal, and a support.

[0058] A fourth embodiment of the present invention provides a catalyst device for purifying exhaust gases using the catalyst system provided in the third embodiment.

[0059] A fifth embodiment of the present invention provides an application of the catalyst system provided in the third embodiment of the present invention or the catalyst device provided in the fourth embodiment of the present invention in automobile exhaust gas purification, industrial exhaust gas treatment or catalytic combustion.

[0060] The present invention will now be further described with reference to specific examples.

[0061] <Comparative Example 1> This comparative example relates to the preparation of a composite oxide based on the molar fraction of cerium oxide, zirconium oxide, and lanthanum oxide, where the molar fraction of cerium oxide, zirconium oxide, and lanthanum oxide is 4:5:1.

[0062] A mixture containing cerium chloride, zirconium oxychloride and lanthanum chloride is preformed. The mixture was added to excess sodium hydroxide to cause precipitation, and the precipitate was filtered and washed. The resulting filter cake was slurried and heated, to which CTAB was added, and the mixture was stirred for 1 hour, after which it was filtered and washed. The resulting product was calcined at 800°C for 3 hours to obtain a cerium-zirconium composite oxide of this component. After calcining this composite oxide at 1100°C for 4 hours, the specific surface area was 15.6 m 2 / g, pore volume was 0.028 mL / g, pore diameter was 2-20 nm, and oxygen storage capacity was 355 μmol O2 / g.

[0063] <Comparative Example 2> This comparative example relates to the preparation of a composite oxide based on the molar fraction of cerium oxide, zirconium oxide, and lanthanum oxide, where the molar fraction of cerium oxide, zirconium oxide, and lanthanum oxide is 4:5:1.

[0064] Two types of chlorine salt solutions were prepared in advance, one of which was mixed solution A containing cerium chloride and zirconium oxychloride, and the other was solution B containing lanthanum chloride. Stoichiometric excess of sodium hydroxide relative to the cations to be precipitated was injected into the reactor. Mixture A was injected into the reactor within 45 minutes, and solution B was injected into the reactor within 15 minutes to obtain a precipitate, which was then subjected to hydrothermal treatment. Lauric acid was added to the resulting suspension, which was stirred for 1 hour, and then filtered and washed. The resulting product was calcined at 800 °C for 3 hours to obtain a cerium-zirconium-based composite oxide of this component. This composite oxide had a specific surface area of ​​20.8 m after calcining at 1100 °C for 4 hours. 2 / g, pore volume was 0.025 mL / g, pore diameter was 2-10 nm, and oxygen storage capacity was 380 μmol O2 / g. <Comparative Example 3>

[0065] This comparative example relates to the preparation of a composite oxide based on the molar fraction of cerium oxide, zirconium oxide, and lanthanum oxide, where the molar fraction of cerium oxide, zirconium oxide, and lanthanum oxide is 3:6:1.

[0066] Two types of nitrate solutions were prepared in advance, one of which was mixed solution A containing zirconium oxychloride and lanthanum chloride, and the other was liquid B containing cerium chloride. Mixture solution A was added to an excess of sodium hydroxide, and the precipitate was filtered and washed to obtain a composite hydroxide containing zirconium and lanthanum. This hydroxide was dispersed in water, liquid B was added thereto, and an excess of aqueous ammonia was further added, and the precipitate was filtered and washed to obtain a composite hydroxide containing cerium, zirconium, and lanthanum. The obtained composite hydroxide was fired at 800°C for 3 hours to obtain a cerium-zirconium composite oxide of this component. After firing at 1100°C for 4 hours, this composite oxide had a specific surface area of ​​21.9 m 2 / g, pore volume was 0.033 mL / g, pore diameter was 2-25 nm, and oxygen storage capacity was 430 μmol O2 / g.

[0067] <Example 1> This example relates to the preparation of a composite oxide containing 50 mol % cerium oxide and 50 mol % zirconium oxide based on the mole fraction of the oxides.

[0068] Two types of mixed chlorine salt solutions were prepared in advance. One was a chlorine salt mixed solution A containing 22 mol% cerium and 28 mol% zirconium in total. The other was a chlorine salt mixed solution B containing the remaining cerium and zirconium in the designed mixture. Mixture A was added to an appropriate amount of sodium hydroxide to cause precipitation. After adding mixture A, liquid B was added thereto, and at the same time sodium hydroxide solution was added to cause precipitation, and the pH was controlled to 9 during the precipitation process. The precipitate was filtered and washed to obtain a composite hydroxide precipitate containing cerium, zirconium, or cerium, zirconium, and optionally one or more metals selected from rare earth salts other than Ce and non-rare earth metal salts other than zirconium. Water was added to the obtained precipitate to make a slurry, which was then heated, a modifier was added thereto, and the mixture was continuously stirred for a while, and then filtered. The obtained filter cake was optionally calcined at 600°C for 3 hours to obtain a cerium-zirconium composite oxide of this component. After calcining at 1100°C for 4 hours, this composite oxide had a specific surface area of ​​36.2 m 2 / g, pore volume was between 0.038 mL / g, pore diameters ranged from 0 to 30 nm, and the oxygen storage capacity was 521 μmol O2 / g.

[0069] <Example 2-11> Unless otherwise specified below, the same method as in Example 1 was used. Specific parameters of the example are shown in Example Parameter Table 1.

[0070] This example relates to the preparation of composite oxides containing cerium oxide, zirconium oxide, or a combination of cerium oxide, zirconium oxide, and one or more rare earth elements (RE) other than cerium (Ce) and non-rare earth elements other than zirconium (Zr) based on mole fraction of the oxides. The composite oxides include the following, expressed as oxides: 10% to 80% cerium oxide in molar terms, 15% to 80% zirconium oxide in molar terms, 0% to 20% of other oxides on a molar basis.

[0071] Two types of mixed chlorine salt solutions are prepared in advance. One is mixed solution A containing one or more metal salts selected from cerium salt, zirconium salt, or cerium salt, zirconium salt, and optionally rare earth salts other than cerium (Ce) and non-rare earth metal salts other than zirconium (Zr), where zirconium accounts for 50 mol % or more of the total zirconium. The other is mixed solution B containing the remaining cerium salt, zirconium salt, or cerium salt, zirconium salt, and optionally rare earth salts other than Ce and non-rare earth metal salts other than zirconium in the designed formulation, where cerium accounts for 50 mol % or more of the total cerium. Mixed solution A was added to an appropriate amount of alkaline substance to cause precipitation. After adding mixed solution A, liquid B was further added thereto, and an alkaline substance was added to cause precipitation. The precipitate was filtered and washed to obtain a composite precipitate containing cerium, zirconium or cerium, zirconium, and optionally one or more of rare earth salts other than Ce and non-rare earth metal salts other than zirconium. Water was added to the obtained precipitate to form a slurry, which was then heated, and a modifier was added thereto, followed by stirring for a while and then filtering. The obtained filter cake was optionally fired at 600-950°C for 3 hours to obtain a cerium-zirconium composite oxide of this component. This composite oxide was fired at 1100°C for 4 hours to obtain a cerium-zirconium composite oxide having a specific surface area of ​​35-55 m. 2 / g, pore volume between 0.03 and 0.2 mL / g, pore diameters between 10 and 30 nm, and oxygen storage capacity of 400 μmol O2 / g or more.

[0072] By comparing the examples provided by the present invention with the comparative examples, it can be seen that the cerium-zirconium composite oxide synthesized by the present invention has a better specific surface area, pore volume, and oxygen storage capacity after aging than the comparative examples, and the pore size distribution after aging is concentrated in the range of 10 to 30 nm, which is more advantageous in terms of catalytic performance. A comparison of specific performances is shown in Table 2.

[0073] JPEG0007634578000002.jpg92170

[0074] JPEG0007634578000003.jpg85170JPEG0007634578000004.jpg13170

[0075] In summary, the present invention relates to a cerium-zirconium composite oxide having gradient distribution of elements and a method for producing the same, a catalyst system using the composite oxide, a catalyst device using the catalyst system for purifying air, and the application of the catalyst system or the catalyst device in purifying automobile exhaust gas, treating industrial exhaust gas, or catalytic combustion. The present invention is to prepare a cerium-zirconium composite oxide having gradient distribution of elements by a stepwise precipitation method, and first precipitate the zirconium-rich component, thereby forming a particle structure and particle deposition structure with high thermal stability, alleviating the surface segregation of zirconium after high-temperature treatment, and reducing the movement of elements between particles. By subsequently precipitating the cerium-rich component, the cerium content of the particle surface layer can be increased, the utilization rate of the cerium element can be improved, and the oxygen storage amount and the oxygen storage and release rate can be increased. The composite oxide prepared by this method has both high thermal stability and high oxygen storage and release performance, so as to meet the requirements for the thermal stability and oxygen storage and release performance of the cerium-zirconium composite oxide due to the long-term use of the catalyst containing the cerium-zirconium composite oxide.

[0076] It should be understood that the above specific embodiments of the present invention are only used to illustratively explain or interpret the principles of the present invention, and do not constitute limitations of the present invention. Therefore, any modifications, equivalent replacements, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. Furthermore, the claims attached to the present invention are intended to cover all changes and modifications included within the scope and boundaries of the attached claims, or equivalent forms of the scope and boundaries.

Claims

1. A cerium-zirconium based composite oxide having gradient element distribution, the composite oxide contains cerium and zirconium, the cerium and zirconium elements being distributed in a gradient from the inside to the outside of the particle; the composite oxide has a cerium oxide content on the particle surface that is higher than the cerium oxide content in the entire composite oxide, a zirconium oxide content on the particle surface that is lower than the zirconium oxide content in the entire composite oxide, the cerium content gradually increases from the inside to the outside in the radial direction of the particle, and the zirconium content gradually decreases from the inside to the outside in the radial direction of the particle, the gradient distribution further includes a gradient distribution of one or more elements selected from rare earth elements other than cerium and / or non-rare earth elements other than zirconium, the gradient distribution being such that the element content gradually decreases or gradually increases from the inside to the outside in the radial direction of the particle, and the content is calculated as a molar content ratio (mol %).

2. The cerium-zirconium-based composite oxide according to claim 1, characterized in that the composite oxide contains the following, expressed as oxides: 10% to 80% cerium oxide in molar terms, 15% to 80% by mole of zirconium oxide, 0% to 20% by mole of other oxides.

3. The cerium-zirconium-based composite oxide according to claim 1, characterized in that the composite oxide contains the following, expressed as oxides: 30% to 60% cerium oxide in molar terms, 30% to 60% zirconium oxide in molar terms.

4. The cerium-zirconium-based composite oxide according to claim 2, characterized in that the other oxides are a combination of one or more elements selected from the group consisting of rare earth elements other than cerium and non-rare earth metal elements other than zirconium, the content of the other oxides in the composite oxide is 2% to 15% in terms of moles, and the oxides of rare earth elements other than cerium account for 70% to 100% of the other oxides.

5. 2. The cerium-zirconium based composite oxide according to claim 1, wherein the composite oxide has a hafnium oxide content of 0.05% to 2% in terms of moles.

6. The cerium-zirconium composite oxide according to claim 4, characterized in that the rare earth elements other than cerium and the non-rare earth metal elements other than zirconium include one or more combinations of lanthanum, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium, yttrium, hafnium, aluminum, barium, manganese, and copper.

7. The cerium-zirconium composite oxide according to any one of claims 1 and 4, characterized in that the rare earth elements other than cerium and the non-rare earth metal elements other than zirconium are a combination of one or more of lanthanum, praseodymium, neodymium, europium, yttrium, hafnium, aluminum, and manganese.

8. 2. The cerium-zirconium based composite oxide according to claim 1, wherein the gradient distribution further includes a gradient distribution in which the content of rare earth elements other than cerium gradually increases from the inside to the outside in the radial direction of the particle.

9. The cerium-zirconium based composite oxide according to claim 4, characterized in that the rare earth elements other than cerium and the non-rare earth metal elements other than zirconium are a combination of one or more of lanthanum, praseodymium, neodymium, europium, yttrium, hafnium, aluminum and manganese.

10. The composite oxide is After heat treatment in air at 1000°C for 4 hours, the specific surface area is 55 to 65 m 2 / g, After heat treatment in air at 1100°C for 4 hours, the specific surface area is 35 to 55 m 2 2. The cerium-zirconium based composite oxide according to claim 1, wherein the zirconium-based composite oxide has a molecular weight of 1.0 to 1.0 g.

11. The composite oxide contains pores of 2 nm to 100 nm, the total pore volume is between 0.1 mL / g and 0.5 mL / g, and the static oxygen storage capacity is ≥ 500 μmol O 2 2. The cerium-zirconium based composite oxide according to claim 1, wherein the zirconium-based composite oxide has a molecular weight of 1.0 to 1.0 g.

12. After calcination at 1100° C. for 4 hours in air, the composite oxide contains pores of 10 nm to 30 nm, the total pore volume is between 0.03 mL / g and 0.2 mL / g, and the static oxygen storage capacity is ≧400 μmol O 2 2. The cerium-zirconium based composite oxide according to claim 1, wherein the zirconium-based composite oxide has a molecular weight of 1.0 to 1.0 g.

13. A method of preparation comprising the steps of: The preparation method is a stepwise precipitation method, (a) precipitation of the first step: mixing an alkaline substance with a mixed solution A containing a cerium salt, a zirconium salt, or a cerium salt, a zirconium salt, and optionally one or more metal salts selected from a rare earth salt other than cerium and a non-rare earth metal salt other than zirconium, stirring and reacting the mixture to obtain a slurry of a precipitate containing the above elements, the zirconium content in the mixed solution A being 60% to 80% of the total zirconium content in terms of molar ratio, the total zirconium content being the content of zirconium added during the entire preparation process; (b) Precipitation of the second step: adding a mixture B of cerium salt, zirconium salt, or one or more metal salts selected from cerium salt, zirconium salt, and optionally rare earth salts other than cerium and non-rare earth metal salts other than zirconium, and an alkaline substance to the slurry obtained in step (a) to precipitate, filtering and washing, and adding water to adjust the slurry to obtain a precipitate slurry containing cerium, zirconium, or cerium, zirconium, and other elements, the cerium in the mixture B occupies 60% to 80% of the total cerium content in terms of molar ratio, the total cerium content being the content of cerium added during the entire preparation process; (c) heating the slurry obtained in the step (b), adding a modifier thereto, filtering the slurry, obtaining a cerium-zirconium-based composite precipitate, and calcining the precipitate at 600° C. to 950° C. to obtain the cerium-zirconium-based composite oxide.

14. The preparation method according to claim 13, characterized in that the salts other than zirconium in the mixed solution A and the mixed solution B are a combination of one or more of nitrates, chlorides, sulfates, and acetates.

15. The preparation method according to claim 13, characterized in that the zirconium salt in the mixed solution A and the mixed solution B is a combination of one or more of zirconium oxide nitrate, zirconium oxide sulfate, zirconium oxide chloride, and zirconium acetate.

16. The preparation method according to claim 13, characterized in that the alkaline material is one or more combinations of sodium hydroxide, ammonium hydroxide, potassium hydroxide, urea, ammonium carbonate, sodium carbonate, sodium bicarbonate.

17. The method according to claim 13, characterized in that the mixed solution A and the mixed solution B each contain 0.2-3 moles of ligand ion per mole of zirconium element, the ligand ion being sulfate anion, and the sulfate anion is provided by adding sulfuric acid or a sulfate salt to the mixed solution A and the mixed solution B.

18. The preparation method according to claim 13, characterized in that the amount of alkaline substance used in the precipitation in the first step is 0.8 to 1.5 times the theoretical amount required for precipitation of cations, and the pH in the precipitation in the second step needs to be controlled within a preset range.

19. 18. The process according to claim 17, characterized in that the ratio of ligand ions to zirconium ions is between 0.5 and 2.

5.

20. The preparation method according to claim 13, characterized in that the modifier comprises one or more of anionic surfactants, nonionic surfactants, polyethylene glycols, carboxylic acids and their salts, and carboxymethylated fatty alcohol ethoxy compound surfactants.

21. 1. A catalyst system comprising: The catalyst system comprises the cerium-zirconium composite oxide according to any one of claims 1 to 12, and at least one of aluminum oxide, a transition metal, a noble metal, and a support.

22. A catalyst device, comprising the catalyst system according to claim 21 for purifying exhaust gas.

23. 22. The application of the catalytic system according to claim 21 in the purification of automobile exhaust gas, the treatment of industrial exhaust gas or catalytic combustion.

Citation Information

Patent Citations

  • Metallic composite oxides material with three hiberarchy and manufacture method thereof

    CN101249438A

  • Cerium-zirconium composite oxide with high specific surface area, and preparation method and application thereof

    CN110252275A

  • Catalyst carrier powder and exhaust gas purification catalyst

    JP2006263550A

  • Method of Controlling Ce:Zr Ratio In Oxide Nanoparticles

    US20120129681A1